(untitled) (Rheumatology Reports, 2011)
The aim of our work is to assess musculoskeletal examination skills of pediatric residents. A self-assessment questionnaire with five-point Likert scale (1=strongly disagree, 5=strongly agree) was used. After completion of questionnaires, the residents were taught proper joint examination techniques. Thereafter, the residents were asked to judge whether they had rated their skills accurately. The session was attended by 25/41 residents (61%). Overall, their reported examination skills were poor with a mean score of 3.0 for PGY1, 2.1 for PGY2, 2.2 for PGY3 and 3.0 for PGY4. After being taught the proper joint examinations techniques, 22% of residents reported they initially overestimated their skills and 5% underestimated their skills. The residents felt most comfortable with the knee exam, least comfortable with the finger and wrist joint exam. Most pediatric residents did not feel they can perform a focused musculoskeletal exam.